Development of Seismic Device for Stainless Steel Rectangular Water Tank at Short Period Earthquake. Issue 3 (16th September 2019) - Aoki, Daisuke; Bando, Yoshiyuki; Watanabe, Naohiko; Suzuki, Moriaki
ABSTRACT: The seismic device effective for an existing stainless steel rectangular water tank was developed to prevent the damage of tank by earthquake, especially focusing on the short period earthquake where the impulsive pressure acts on the side wall of tank. The seismic device consisted of a thin high damping rubber plate, sandwiched with two metal plates, which were attached on both the surfaces of the rubber plate. These seismic devices were expected to be set between the base frame of tank and the anchor block. First, a shaking table test of a small water tank (1, 000 mm×1, 000 mm×1, 000 mm) made of stainless steel panels was performed under the several conditions of the number, shape and rubber thickness of the seismic devices. Then, eight seismic devices were set to a large water tank (3, 000 mm×3, 000 mm×3, 000 mm) constructed from nine stainless steel panels for each side wall. These tanks were put on the shaking tables and dynamic shaking tests were performed. The shaking frequency was varied from DC to 12 Hz with a given interval step and the water pressure on the side wall of tank was measured. In this study, by setting the seismic devices to both the small and large water tanks, the natural impulsive frequencies of tanks became a little lower, and the impulsive pressure at the natural frequency became smaller with increasing rubber thickness and with increasing surface pressure. When the HYOGOKEN‐NANBU earthquake waves were given to the large water tank with the seismic devices, the impulsive pressure at the short period oscillation was largely suppressed but the sloshing pressure at the long period oscillation was scarcely enhanced.